Developing Employees’ Innovation Competence Through Organizational Development Intervention: A Case Study of Logis Company in China - Ma, Jie; Lu, Lee Hsing (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
This study aims to propose a systematic organizational development project to improve Individual Innovation Competence of employees by enhancing Perceived Innovative Organizational Culture, Affective Commitment, and Self-efficacy with Tacit Knowledge Sharing as the mediating variable. The researcher adopted action research on the focal company to test how Individual Innovation Competence can be improved by applying Organizational Development Intervention (ODI) measures to engage employees and promote Perceived Innovative Organizational Culture, Affective Commitment, Self-efficacy, and Tacit Knowledge Sharing. The stages of ODI are designed according to the framework of activities contributing to effective changing management, which contains five stages: motivating change, creating a vision, developing support, managing the transition, and sustaining momentum. Mixed methods were used to collect data by the close-ended questionnaire and the semi-structured interview before and after the ODI. Quantitative data was analyzed by Linear regression and Wilcoxon signed rank test to validate the hypotheses. The results indicated that Perceived Innovative Organizational Culture, Affective Commitment, Self-efficacy, Tacit Knowledge Sharing, and Individual innovation competence had significantly improved after the ODI. And Perceived Innovative Organizational Culture, Affective Commitment, and Self-efficacy positively correlate with Tacit Knowledge Sharing and Individual innovation competence. Tacit Knowledge Sharing positively correlates with Individual Innovation Competence and has a partially mediating effect on Perceived Innovative Organizational Culture, Affective Commitment, Self-efficacy to Individual Innovation Competence. Finally, an organizational development project is proposed for enhancing employees’ innovation competence.